2003
DOI: 10.1890/1051-0761(2003)013[0842:dmatoh]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Defining Macroinvertebrate Assemblage Types of Headwater Streams: Implications for Bioassessment and Conservation

Abstract: We used data from 235 boreal headwater streams in Finland to examine whether macroinvertebrate assemblages constitute clearly definable types, and how well biologically defined assemblage types can be predicted using environmental variables. Twoway indicator species analysis produced 10 assemblage types, which differed significantly from each other (multiresponse permutation procedure, MRPP). However, based on MRPP and nonmetric multidimensional scaling, there was wide variation among sites within each assembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
83
0
7

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(100 citation statements)
references
References 46 publications
10
83
0
7
Order By: Relevance
“…Because perceptions about which environmental factors are most strongly related to assemblage composition depend in part on the spatial extent of observation (Marchant et al, 1999;Sandin and Johnson, 2004;Bonada et al, 2005;Johnson et al, 2007), we expected that we might find some consistencies and some differences between results of our study and those of other large-scale or national studies from elsewhere in the world. With ordinations based on invertebrates being identified to the finest practical level, we and others (Marchant et al, 1999;Turak et al, 1999;Heino et al, 2003;Lorenz et al, 2004;Sandin and Johnson, 2004) found a prominent relationship between invertebrate assemblage composition and geographic position (e.g. latitude and/or longitude).…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Because perceptions about which environmental factors are most strongly related to assemblage composition depend in part on the spatial extent of observation (Marchant et al, 1999;Sandin and Johnson, 2004;Bonada et al, 2005;Johnson et al, 2007), we expected that we might find some consistencies and some differences between results of our study and those of other large-scale or national studies from elsewhere in the world. With ordinations based on invertebrates being identified to the finest practical level, we and others (Marchant et al, 1999;Turak et al, 1999;Heino et al, 2003;Lorenz et al, 2004;Sandin and Johnson, 2004) found a prominent relationship between invertebrate assemblage composition and geographic position (e.g. latitude and/or longitude).…”
Section: Discussionsupporting
confidence: 48%
“…However, understanding the major factors relating to assemblage composition at a broad scale can give context to our understanding of factors controlling assemblages at smaller scales of observation. Regional or national macroinvertebrate assemblage patterns in streams least disturbed by human activities have been examined in Europe Heino et al, 2003;Lorenz et al, 2004;Sandin and Johnson, 2004), Australia (Marchant et al, 1999;Smith et al, 1999;Turak et al, 1999), and North America (Waite et al, 2000). Examinations of assemblage patterns at even larger spatial scales are not often attempted because of the difficulty of collecting a large number of samples over a wide area, and collecting and analyzing samples and data in a consistent manner.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, macroinvertebrate distributions were mainly . In numerous studies (e.g., Miserendino 2001;Heino et al 2003;Soldner et al 2004), altitude and water chemistry always related to the macroinvertebrate assemblages. Altitude directly determines some environmental factors such as temperature and illumination in a region.…”
Section: à2mentioning
confidence: 99%
“…In addition, there were no signficant differences in taxa richness and total abundance among stream types. Finally, CA ordination plots showed no easily identifiable groups and a great overlap between predefined types might be indicative of a weak classification when all the assemblage is used (see Heino et al, 2003;Heino and Mykra, 2006). Verdonschot and Nijboer (2004) indicate that differences between stream types are only partly explained by qualitative differences in species lists but are also influenced by differences in abundances of individual species.…”
Section: Ecological Meaning Of the Mondego Stream Typesmentioning
confidence: 99%
“…Since catchment geomorphology and climate-related variables are often strong predictors of macroinvertebrate assemblages (Richards et al, 1996;Hawkins et al, 2000;Verdonschot and Nijboer, 2004;Chaves et al, 2005), sites within the same WFD type that were based on these factors are expected to represent relatively distinct ecological units for invertebrate communities (Verdonschot, 2006a;Sa´nchez-Montoya et al, 2007). Alternatively, in bottomup approaches, aquatic biological data are used to group similar stream sites (e.g., Wright et al, 1984;Parsons and Norris, 1996;Marchant et al, 1997;Ehlert et al, 2002;Heino et al, 2003;Lorenz et al, 2004;Dodkins et al, 2005;Sa´nchez-Montoya et al, 2007). To accomplish this purpose biotic data should be collected in reference sites since anthropogenic stress reduces natural differences between communities (Verdonschot, 2006a).…”
Section: Introductionmentioning
confidence: 99%